Gonyaulax whaseongensis sp. nov. (Gonyaulacales, Dinophyceae), a new phototrophic species from Korean coastal waters. Issue 6 (22nd October 2018) - Lim, An Suk; Jeong, Hae Jin; Kwon, Ji Eun; Lee, Sung Yeon; Kim, Ji Hye
Abstract : The planktonic phototrophic dinoflagellate Gonyaulax whaseongensis sp. nov., isolated from coastal waters of western Korea, was described from living and fixed cells under light and scanning electron microscopy, and its rDNA was sequenced. Gonyaulax whaseongensis had a plate formula of 2pr, 4′, 6′′, 6c, 6′′′, 1p, and 1′′′′ with S‐type ventral organization like the other species in the genus. However, this dinoflagellate had a narrow cingulum (ca. 2.6 μm), small displacement of the cingulum, slight overhang and steep angle between the ends of the cingulum, quadrangular sixth precingular plate, reticulated cell surface without longitudinal lines or ridges, and two unequal antapical spines, together which distinguish this from all other reported Gonyaulax species. In addition, the SSU and LSU rDNA sequences were 8%–12% and 11%–24%, respectively, different from those of Gonyaulax polygramma, Gonyaulax spinifera, Gonyaulax fragilis, Gonyaulax membranacea, and Gonyaulax digitale, the putatively closest related species in the phylogenetic analysis.